Call for action: incorporating wellness practices into a holistic management plan for rheumatoid arthritis – going beyond treat-to-target - Taylor, P; Van de Laar, M; Laster, A; Fakhouri, W; Quebe, A; de la Torre, I; Jain, S (BMJ Publishing Group, 2021)
This expert opinion article explores the strategy of adopting a holistic approach to the management of rheumatoid arthritis (RA) by incorporating the wellness practices of exercise, optimised sleep, optimised nutrition, mindfulness, social connectedness and positive emotions into the management plan. The aim is to attain optimal health for each patient beyond that achievable by limiting disease management to pharmacological treatment to attain the lowest achievable composite scores of disease activity, as recommended with the current treat-to-target approach, and addressing the recent recognition of pain control as a key patient-reported outcome. Incorporating wellness practices into a busy clinical setting requires creativity and customisation based on the individual practice setting and the individual needs of each patient. Such practices can help people living with RA to achieve optimum wellness through the introduction of measures—according to individual need—designed to improve the aspects of life most impacted for that person, thereby complementing treat-to-target and pain control strategies with pharmacological agents. Clinicians must consider wellness practices in addition to treat-to-target pharmacological agents for the holistic management of people with RA.